Investigation on the long-duration tribological performance of bilayered diamond/diamond-like carbon films. (June 2014) - Shen, Bin; Chen, Sulin; Sun, Fanghong
The long-duration tribological performance of two bilayered diamond/diamond-like carbon films, namely microcrystalline diamond/diamond-like carbon and nanocrystalline diamond/diamond-like carbon films, is evaluated in 24-h dry sliding against the silicon nitride counterpart ball, in terms of the stable coefficient of friction, the sliding stability, and the specific wear rate of both the film and counterpart surface. Moreover, their sliding behaviors are illustrated from the aspect of sliding interface evolution. Characterization results indicate that the top-layered diamond-like carbon films significantly reduce the surface roughness of single-layered diamond film and determine the surface property of composite film. For the tribological performance, the top-layered diamond-like carbon coating significantly reduces the stable friction coefficient of the microcrystalline diamond film by 10–34%, but does not exhibit a similar effect on the nanocrystalline diamond film due to the severe delamination of diamond-like carbon coating. Either, the top-layered diamond-like carbon film does not show noticeable benefit on enhancing the sliding stability or wear resistance of single-layered diamond coating. The delamination of top-layered diamond-like carbon coating is supposed to play a critical role on such phenomenon. Furthermore, an enhanced tribomap is developed that is capable of providing a visualized and highly customized evaluation on tribological performance of sliding contacts according to the specific requirements a variety of applications. According to this tribomap, nanocrystalline diamond film always shows the superior performance to others.